Synthesis and evaluation of novel naphthol diazenyl scaffold based Schiff bases as potential antimicrobial and cytotoxic agents against human colorectal carcinoma cell line (HT-29) - Harmeet Kaur; Jasbir Singh; Balasubramanian Narasimhan (BMC Chemistry, 2019)
Abstract Background In search of new antimicrobial and cytotoxic agents, a series of new naphthol diazenyl scaffold based Schiff bases (NS1–NS23) was efficiently synthesized by condensation of 2-hydroxy naphthaldehyde azo dyes with various substituted aromatic/heteroaromatic/aliphatic amines. Methodology The synthesized derivatives were characterized by various physicochemical and spectral techniques and assessed for in vitro antimicrobial and cytotoxic potential against human colorectal carcinoma cell line (HT-29). The active derivatives were further evaluated for their apoptotic potential by Annexin-V/propidium iodide double staining assay using flow cytometer and analyzed for cell-cycle arrest studies. Results and conclusion The derivative NS-2 was found maximum active against E. coli, S. enterica and B. subtilis. The derivatives NS-12, NS-15, NS-21, and NS-23 showed maximum antifungal activity against A. fumigatus. The maximum cytotoxicity was observed from the derivatives NS-2, NS-8, NS-21, and NS-23 towards HT-29 cell line with IC50 between 4 and 19 μg/ml. More than 90% and 62% of the cells were found in the apoptotic phase on treatment with NS-2 and NS-21 respectively in comparison to the 68% for doxorubicin. Further, these derivatives arrested the cell growth in S and G2/M phase of the cell cycle.